Road Line and Direction Detection Methods Based on Vanishing Point for an Electric Vehicle - Yildirim, Merve; Karaduman, Ozgur; Kurum, Hasan (Ieee, 2024)
Image road detection is a significant problem in the applications of autonomous vehicles and mobile robots. The bend direction and angle are the main subjects for the inclined roads. To move safely on the road, it is very important to determine the road lines and the direction of the bend. For this reason, a Vanishing Point (VP) detection algorithm is proposed to estimate the road boundaries for an Electric Vehicle (EV). However, it is challenging to effectively estimate the VP from a video image of the inclined roads. Therefore, a reliable VP estimate approach is suggested that makes use of the junction points of the line segments taken from an image and a probabilistic voting process. Besides, the OpenCV library, which has widely used computer vision algorithms and the Python software language, is utilized in the study. As a result, a Driver Assistance System (DAS), which is an important step in autonomous driving, is developed, and safe driving is provided by this work.
6th Global Power, Energy and Communication Conference (GPECOM) -- JUN 04-07, 2024 -- Budapest, HUNGARY
Keywords: electric vehicle; image processing; python; OpenCV; road line detection; direction detection; vanishing point